Development of next-generation respiratory virus vaccines through targeted modifications to viral immunomodulatory genes. (2nd December 2015) - Stobart, Christopher C; Moore, Martin L
Abstract : Vaccines represent one of the greatest contributions of the scientific community to global health. Yet, many pathogens remain either unchallenged or inadequately hindered by commercially available vaccines. Respiratory viruses pose distinct and difficult challenges due to their ability to rapidly spread, adapt, and modify the host immune response. Considerable research has been directed to understand the role of respiratory virus immunomodulatory proteins and how they influence the host immune response. We review here efforts to develop next-generation vaccines through targeting these key immunomodulatory genes in influenza virus, coronaviruses, respiratory syncytial virus, measles virus, and mumps virus.